Head teachers’ Supervision of Curriculum Implementation: Implications on Provision of Quality Secondary Education in Kenya - Awiti, Jennipher Atieno; Onderi, Henry Nyabuto; Raburu, Pamela (Advances in Social Sciences Research Journal, 2016)
This study sought to find out how the head teachers’ supervision of curriculum implementation influences provision of quality education in Kisumu East Sub-County Secondary schools, Kenya. The study population consisted of 13 public and 4 private secondary schools in Kisumu East Sub-County. The total population of the study was 1114. Out of these 924 were Form Four candidates, 174 teachers and 17 head teachers. The study used a sample size of 382 consisting of 308 Form Four candidates, 58 teachers selected using simple random sampling. A total of 16 head teachers were selected using purposive sampling technique. The instrument validity was ascertained by use of a four-point scale rating by experienced colleagues to ascertain the relevance of the questions while instrument reliability was ascertained using Split-Half Technique. Piloting was done in 4 schools in the neighboring Kisumu Central Sub-County to ascertain Face validity of the instruments. The research design employed in the study was descriptive survey.  Questionnaires, interviews and document analysis were used to obtain data. Quantitative data analysis was done using descriptive and inferential statistics with the aid of SPSS version 21 and co-relational techniques. Qualitative data from interviews were analyzed using Thematic Analysis. The findings of the study indicated that there was a strong relationship between head teacher supervision, curriculum implementation and provision of quality education in Kisumu East Sub-County. Challenges faced by head teachers included teacher and student truancy, teacher resistance to supervision exercise, financial constraints hampering quality education provision, interschool transfers and high student dropout rate among others. The study recommended that the head teachers, as internal Quality Assurance Officers at the school level should attend supervision training sessions offered by Kenya Educational Management Institute.